Non-Reacting Spray Characteristics of Gasoline and Diesel With a Heavy-Duty Single-Hole Injector - Tzanetakis, Tom; Johnson, Jaclyn; Schmidt, Henry; Atkinson, William; Naber, Jeffrey (Frontiers in Mechanical Engineering, 2022)
Gasoline compression ignition (GCI) is a promising combustion technology that could help alleviate the projected demand for diesel in commercial transport while providing a pathway to achieve upcoming CO2 and criteria pollutant regulations for heavy-duty engines. However, relatively high (i.e., diesel-like) injection pressures are needed to enable GCI across the entire load range while maintaining soot emissions benefits and managing heat release rates. There have only been a limited number of previous studies investigating the spray characteristics of light distillates with high-pressure direct-injection hardware under charge gas conditions relevant to heavy-duty applications. The current work aims to address this issue while providing experimental data needed for calibrating spray models used in simulation-led design activities. The non-reacting spray characteristics of two gasoline-like fuels relevant to GCI were studied and compared to ultra-low-sulfur diesel (ULSD). These fuels shared similar physical properties and were thus differentiated based on their research octane number (RON). Although RON60 and RON92 had different reactivities, it was hypothesized that they would exhibit similar non-reacting spray characteristics due to their physical similarities. Experiments were conducted in an optically accessible, constant volume combustion chamber using a single-hole injector representing high-pressure, common-rail fuel systems. Shadowgraph and Mie-scattering techniques were employed to measure the spray dispersion angles and penetration lengths under both non-vaporizing and vaporizing conditions. Gasoline-like fuels exhibited similar or larger non-vaporizing dispersion angle compared to ULSD. All fuels followed a typical correlation based on air-to-fuel density ratio indicating that liquid density is the main governing fuel parameter. Injection pressure had a negligible effect on the dispersion angle. Gasoline-like fuels had slower non-vaporizing penetration rates compared to ULSD, primarily due to their larger dispersion angles. As evidenced by the collapse of data onto a non-dimensional penetration correlation over a wide range of test conditions, all fuels conformed to the expected physical theory governing non-vaporizing sprays. There was no significant trend in the vaporizing dispersion angle with respect to fuel type which remained relatively constant across the entire charge gas temperature range of 800–1200 K. There was also no discernable difference in vapor penetration among the fuels or across charge temperature. The liquid length of gasoline-like fuels was much shorter than ULSD and exhibited no dependence on charge temperature at a given charge gas pressure. This behavior was attributed to gasoline being limited by interphase transport as opposed to mixing or air entrainment rates during its evaporation process. RON92 had a larger non-vaporizing dispersion angle but similar penetration compared to RON60. Although this seems to violate the original similarity hypothesis for these fuels, the analysis was made difficult due to the use of different injector builds for the experiments. However, RON92 did show a slightly larger vapor dispersion angle than RON60 and ULSD. This observation was attributed to nuanced volatility differences between the gasoline-like fuels and indicates that vapor dispersion angle likely relies on a more complex correlation beyond that of only air-to-fuel density ratio. Finally, RON92 showed the same quantitative liquid length and insensitivity to charge gas temperature as RON60.